2013
DOI: 10.1111/inm.12035
|View full text |Cite
|
Sign up to set email alerts
|

Transition to a smoke‐free culture within mental health and drug and alcohol services: A survey of key stakeholders

Abstract: Tobacco smoking is common among people with mental illnesses, and they carry a higher burden of smoking-related illnesses. Despite this, smoke-free policies and systems for supporting cessation have proved difficult to introduce in mental health and drug and alcohol services (MHDAS). This paper examines the barriers to becoming smoke free within New Zealand services. Key informants, including staff, smoke-free coordinators, and cessation specialists were interviewed. Of the 142 invited informants 61 agreed (42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 20 publications
(23 reference statements)
1
38
0
Order By: Relevance
“…All studies included stated clear research questions or objective, and in all but one study (which did not provide the requisite information in the published report 36), data were judged to be sufficient to address the stated research questions or objectives (however, this study provided relevant for the current review and was therefore included here).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All studies included stated clear research questions or objective, and in all but one study (which did not provide the requisite information in the published report 36), data were judged to be sufficient to address the stated research questions or objectives (however, this study provided relevant for the current review and was therefore included here).…”
Section: Resultsmentioning
confidence: 99%
“…This perception appeared to arise from beliefs that patients would not be interested in quitting smoking 39, 40, 41, 42, that patients would be unable to quit smoking successfully 35, 36, 40 and the view that smoking cessation would be too much for patients to cope with alongside their other issues 36, 39, 41, 42, 43. A minority of studies reported concerns about the negative consequences of quitting smoking, such as concerns about a negative impact on psychiatric symptoms/abstinence 36, 41, the potential effects on medication 36 and a fear that smoking cessation may make patients violent 36.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations